Reporting Interaction Effects: Visualization, Effect Size, and Interpretation. (November 2022) - Murphy, Kevin R.; Aguinis, Herman
Most management theories include hypotheses about interaction effects (i.e., the relation between two variables depends on values of another), but it is common for articles to present results that make it difficult to evaluate the nature, strength, and importance of the effect. We offer recommendations for improving the reporting of interaction effects by focusing on (a) visualizations, (b) effect size estimates, and (c) assessments of the nature, meaning, and importance of interactions for theory and practice.